Combining single source chemical vapour deposition precursors to explore the phase space of titanium oxynitride thin films. Issue 31 (14th February 2018) - Rees, Kelly; Lorusso, Emanuela; Cosham, Samuel D.; Kulak, Alexander N.; Hyett, Geoffrey
Abstract : Combining single-source precursors in aerosol assisted CVD allows control of the composition of mixed anion titanium oxynitride thin films. Abstract : In this paper we report on a novel chemical vapour deposition approach to the formation and control of composition of mixed anion materials, as applied to titanium oxynitride thin films. The method used is the aerosol assisted chemical vapour deposition (AACVD) of a mixture of single source precursors. To explore the titanium–oxygen–nitrogen system the single source precursors selected were tetrakis(dimethylamido) titanium and titanium tetraisopropoxide which individually are precursors to thin films of titanium nitride and titanium dioxide respectively. However, by combining these precursors in specific ratios in a series of AACVD reactions at 400 °C, we are able to deposit thin films of titanium oxynitride with three different structure types and a wide range of compositions. Using this precursor system we can observe films of nitrogen doped anatase, with 25% anion doping of nitrogen; a new composition of pseudobrookite titanium oxynitride with a composition of Ti3 O3.5 N1.5, identified as being a UV photocatalyst; and rock-salt titanium oxynitride in the range TiO0.41 N0.59 to TiO0.05 N0.95 . The films were characterised using GIXRD, WDX and UV-vis spectroscopy, and in the case of the pseudobrookite films, assessed for photocatalytic activity. This work shows that a so-called dual single-source CVD approach is an effective method for the deposition of ternary mixed anion ceramic films through simple control of the ratio of the precursors, while keeping all other experimental parameters constant.